2022
DOI: 10.1186/s12883-022-02605-5
|View full text |Cite
|
Sign up to set email alerts
|

Detrimental effect of increased blood pressure variability on clinical outcome in acute ischemic stroke treated with reperfusion therapy: a case control study

Abstract: Background Blood pressure variability (BPV) is related to clinical outcome in acute ischemic stroke (AIS) treated with reperfusion therapy, but still is not included in clinical practice. This study aims to associate BPV during the first week of AIS with the outcome at three months. Methods We included 236 AIS patients treated with reperfusion therapy, and then divided them into good outcome and poor outcome groups. BPV measurements, including stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…However, according to an individual patient data meta-analysis that included 2460 patient data derived from five observational studies, systolic BPV within the first 24 h post-EVT, as expressed by the highest tertile of both standard deviation and coefficient of variation, was associated with higher mortality and disability at 3 months, independently of the mean systolic BP levels [86]. These results were further confirmed by several other cohort studies during the last few years (Table 2) [87][88][89][90], highlighting that the association of BPV with adverse clinical outcomes may even be intensified among patients receiving general anesthesia [91] or additional rescue treatment with balloon angioplasty or stenting [92]. One study-level meta-analysis that included 11 studies comprising more than 3500 patients, confirmed that higher systolic BPV was associated with lower odds of achieving good functional outcomes at 3 months [93].…”
Section: Blood Pressure Variability Among Patients With Acute Ischaem...mentioning
confidence: 61%
“…However, according to an individual patient data meta-analysis that included 2460 patient data derived from five observational studies, systolic BPV within the first 24 h post-EVT, as expressed by the highest tertile of both standard deviation and coefficient of variation, was associated with higher mortality and disability at 3 months, independently of the mean systolic BP levels [86]. These results were further confirmed by several other cohort studies during the last few years (Table 2) [87][88][89][90], highlighting that the association of BPV with adverse clinical outcomes may even be intensified among patients receiving general anesthesia [91] or additional rescue treatment with balloon angioplasty or stenting [92]. One study-level meta-analysis that included 11 studies comprising more than 3500 patients, confirmed that higher systolic BPV was associated with lower odds of achieving good functional outcomes at 3 months [93].…”
Section: Blood Pressure Variability Among Patients With Acute Ischaem...mentioning
confidence: 61%